From Ethnocentrism to Cosmopolitanism: Exploring Tourist Motivationthrough Cultural Intelligence and Global Literacy - Chunyu Zhao; Urandelger Gantulga; Chunyun Wang; Enkh-Amgalan Byambajav (SCAD Independent, 2026)
International travel motivation is often explained through binary cultural orientations, with ethnocentrism viewed as a barrier and cosmopolitanism as a facilitator of global mobility. This study aims to reassess this assumption by examining international travel motivation through an integrated framework that combines cultural orientations and global competence perspectives. Adopting a quantitative approach, this study uses survey data collected from Chinese tourists and analyzes the data through moderated regression analysis to examine the direct effects of ethnocentrism and cosmopolitanism on international travel motivation, as well as the moderating roles of global literacy and cultural intelligence. The findings reveal that both ethnocentrism and cosmopolitanism positively influence international travel motivation. Global literacy significantly strengthens these relationships, indicating its role as a key cognitive mechanism enabling culturally rooted individuals to engage in global mobility. In contrast, cultural intelligence does not show a significant moderating effect, suggesting that its relevance lies primarily in post-travel adaptation rather than in the formation of travel intentions. This study contributes by reconceptualizing tourist ethnocentrism as a conditional motivational resource and by clarifying the distinct roles of global literacy and cultural intelligence within global competence research, with implications for tourism policy and international mobility in globalizing societies.